Prenatal stress: course and interrelation of emotional and physiological stress measures - Rothenberger, Steffi Elena; Moehler, Eva; Reck, Corinna; Resch, Franz (Psychopathology, 2011)
Background: Prenatal stress is known to be a potential risk factor for cognitive, behavioural and motor development that even last until adolescence. A consensus of how ‘prenatal stress’ can be measured, in which trimester of pregnancy women should be studied and whether subjective feelings of being stressed are associated with a hormonal response is still lacking. To close this gap, a prospective longitudinal study was conducted in pregnant women. Sampling and Methods: 108 subjects were asked to fill out questionnaires concerning pregnancy-related anxiety, perceived stress, marital satisfaction, critical life events and to collect salivary cortisol in each trimester of pregnancy. Results: Fear of giving birth increases until the end of pregnancy, and marital satisfaction is highest at the end of pregnancy. Perceived stress is related to a hormonal response in cortisol only in the first (r = 0.18, p < 0.10) and second (r = 0.18, p < 0.10) trimesters of pregnancy. Critical life events are linked to raised cortisol levels in early pregnancy only (r = 0.28, p < 0.01). Conclusion: Prenatal stress can be operationalized by using different subjective as well as physiological stress measures. Only in the first half of pregnancy self-report and physiological stress measures seem to be associated.
Published online: November 11, 2010
Gesehen am 20.09.2022